Steroidogenesis in Leydig cells: effects of aging and environmental factors. Issue 4 (October 2017) - Wang, Yiyan; Chen, Fenfen; Ye, Leping; Zirkin, Barry; Chen, Haolin
Abstract : Serum testosterone (TS) levels decrease with aging in both humans and rodents. Using the rat as a model system, it was found that age-related reductions in serum TS were not due to loss of Leydig cells, but rather to the reduced ability of the Leydig cells to produce TS in response to luteinizing hormone (LH). Detailed analyses of the steroidogenic pathway have suggested that two defects along the pathway, LH-stimulated cAMP production and cholesterol transport to and into the mitochondria, are of particular importance in age-related reductions in TS production. Although the mechanisms involved in these defects are far from certain, increasing oxidative stress appears to play a particularly important role. Interestingly, increased oxidative stress also appears to be involved in the suppressive effects of endocrine disruptors on Leydig cell TS production.